(untitled) (Hoboken, N.J, 2004)
Provides useful descriptions of applications for the reader to apply in his/her research into materials, polymers, and medicine/drug development. Covers non-linear optical materials, speciality magnetic materials, liquid crystals, anticancer and antiviral drugs, treatment of arthritis, antibacterial drugs, antifouling materials, treatment of certain vitamin deficiencies, electrical conductors and semiconductors, piezoelectronic materials, electrodes, UV absorption applications, super-strength materials, special lubricants and gaskets, selective catalytic and multisite catalytic agents.
Keywords: Ferrocene,Organometallic polymers,Organoiron compounds,Macromolecules,Metal complexes,Ferrocene - tên một loại phụ gia,Hợp chất cao phân tử hữu cơ,Hợp chất hữu cơ,Đại phân tử,Phức hệ kim loại